Food, rural, agricultural and fisheries policies in Turkey - Cakmak E.H.; Eruygur O.H. (Les agricultures méditerranéennes : analyses par pays, 2008)
Turkey has embarked on an ongoing structural adjustment and stabilization program in 1999. Agricultural policies have been selected to undergo heavy adjustments due to the ineffective set of tools and their ever increasing burden on government expenditures. Even without the macroeconomic stabilization program, several additional factors would have forced Turkey to enter into a phase of agricultural policy reform. New round of negotiations for the renewal of the WTO-Agreement on Agriculture is expected to be a challenging process. Despite recent changes in the policy framework in Turkey, the issue of alternative policy tools in agriculture will remain as a major item in the agricultural agenda. Turkey’s candidacy for membership to EU has also added a new dimension to the deliberations on agriculture and related policies. This paper aims to assess recent developments in the agro-food sector and related policy changes. Next section is devoted to a broad overview of macroeconomic and agricultural developments in Turkey. More detailed analyses of the recent progress in the agro-food sector encompassing production, consumption and trade are presented in the second section. This section includes the structure and characteristics of the food and beverage industry. The third section provides the basics of fishing in Turkey, together with fishing fleet structure, total catches and trade in fisheries. The fourth section covers all agriculture related policies. A quick overview of rural, trade, price and environmental policies can be found in this section. Finally, the last section is reserved for concluding remarks.